Introduktion til Det Pragmatiske Hjul – En ny tilgang til Direktiver - Durst-Andersen, Per (Ny forskning i grammatik, 2016)
It will be argued that, despite their obvious anchoring in verbal communication based on linguistic signs (symbols), Directives, i.e. Requests and Offers, have more in common with gestures which primarily involve indexes and icons. It will be demonstrated that this type of speech act should be interpreted as consisting of three indexical sign types: (1) a symptom that points at the speaker and goes back in time; (2) a signal that points at the hearer and goes forward in time; and (3) a model that points at a situation and is timeless, because it can be used at any time. On this basis, a speech act process model for communicationbased problem solving is created specifically for declarative Directives.